2016
DOI: 10.1371/journal.pone.0162221
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 Is Present at High Levels in Wound Fluid from Breast Cancer Patients Immediately Post-Surgery, and Is Not Increased by Intraoperative Radiation Therapy (IORT)

Abstract: In patients with low-risk breast cancer, intraoperative radiotherapy (IORT) during breast-conserving surgery is a novel and convenient treatment option for delivering a single high dose of irradiation directly to the tumour bed. However, edema and fibrosis can develop after surgery and radiotherapy, which can subsequently impair quality of life. TGF- β is a strong inducer of the extracellular matrix component hyaluronan (HA). TGF-β expression and HA metabolism can be modulated by irradiation experimentally, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
2
11
0
Order By: Relevance
“…Our finding is supported by El-Aziz et al, [17] who revealed that the level of TGF-β was considerably higher in malignant groups than normal control group with p value (<0.0001). The results of the present study was supported by Scherer et al, [18] who detected the level of TGF-β in breast cancer patients; he found that its level was increased. In the current study, ROC curve of beclin-1 showed 95% sensitivity and 98.5% specificity and this is supported by Harb, et al, [19] who reported that the sensitivity of beclin-1 as a predictor for advanced stage of IDC was 85.5% and the specificity was 98.5%.…”
Section: Correlation Between Beclin-1 and Tgf-β Expression Levelssupporting
confidence: 88%
“…Our finding is supported by El-Aziz et al, [17] who revealed that the level of TGF-β was considerably higher in malignant groups than normal control group with p value (<0.0001). The results of the present study was supported by Scherer et al, [18] who detected the level of TGF-β in breast cancer patients; he found that its level was increased. In the current study, ROC curve of beclin-1 showed 95% sensitivity and 98.5% specificity and this is supported by Harb, et al, [19] who reported that the sensitivity of beclin-1 as a predictor for advanced stage of IDC was 85.5% and the specificity was 98.5%.…”
Section: Correlation Between Beclin-1 and Tgf-β Expression Levelssupporting
confidence: 88%
“…Boothe et al reported that TGF-β1 serum levels of breast cancer patients can be used as an early biomarker for radiation-induced fibrosis post RT [44]. Evidence was also found for a high level of TGF-β1 in the breast cancer patients' wound fluids 24 h following surgery [45].…”
Section: The Role Of Signalling Molecules and Radiation Responsementioning
confidence: 99%
“…High plasma or serum levels of TGF-β1 before RT have been associated with fibrosis of the breast [ 4 , 5 ]. Regardless of whether patients received intra-operative RT or not, TGF-β1 concentrations in wound fluid were similar 24 h after surgery [ 7 ]. The relationship between TGF-β1 and RT has been most extensively studied in lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%